Tell Barri/Kahat: la campagna del 2000 - Paolo Emilio, Pecorella (Firenze University Press, 2003)
In the plains of north-eastern Syria, not far from the course of the Tigris, is the site of Tell Barri, identified with the city of Kahat, a centre famous in the course of the second millennium for the presence of the temple of the god of the storm and for the palace of Tukulti-Ninurta II, an Assyrian sovereign of the ninth century BC. The archaeological sequence which has been brought to light stretches from the start of the third millennium up to the fourteenth century AD. From the Sumerian, Accadian, Paleo-Babylonian and Assyrian evidence through to the Achemenidian, Hellenistic, Parthian, Sassanid-Byzantine and finally mediaeval occupation. The book illustrates the results of the seventeenth excavation campaign, carried out by the group from the University of Florence and from the "Federico II" University of Naples.